Bonding social capital posession among kelantan chinese muslim - Mohd Ali, Adi Syahid; Amir Zal, W.A (Universiti Sultan Zainal Abidin (UNISZA), 2018)
This paper focuses on bonding social capital possession among Chinese Muslims in Kelantan. Chinese Muslim community seems to have conflicts in their bonding social capital. Bonding social capital in this paper can be defined as the relationships that the Chinese Muslim community have with their non- Muslim family members. This research was carried out using the sequential explanatory mixed method design involving the Kelantan Chinese Muslim community with 75 respondents selected for quantitative and 5 respondents for qualitative research methods. The sampling methods adopted were convenient and snowball samplings. The research data were collected using questionnaires and semi structured interviews. The findings show that bonding social capital was at intimate level before converting to Islam and changed to moderately intimate after they had converted to Islam. This may indicate that Chinese Muslim community in this study had conflicts in their bonding social capital. The findings also have confirmed that there are significant differences between social capital possession before and after converting to Islam and no significant differences for the bonding social capital possession based on the period they convert to Islam. While qualitative data affirm the differences in Chinese Muslim bonding social capital, the data further explain that the bonding social capital possession was changed not due to conflict after conversion but because of the differences in practices and beliefs, which had significantly impact their bonding social capital. Thus, effort to enhance bonding social capital capacity must be done so that differences between religions will not become an obstacle to a healthy and continuous relationship between Chinese Muslim and their non-Muslim family members.